Evidence-Based Practice in Nursing: A Systematic Literature Review of Barriers and Facilitators of Implementation - Aeshah Abdu Ahmed Hadadi, Fatimah Hassan Al Abbas, Afnan Ali Ahmed Almusharraf, Layla Hassan Ghanem Alghanem (International Journal of Scientific Research and Innovative Studies, 2024)
One of the greatest paradigm shifts that has been discovered in the contemporary nursing practice is evidence-based practice (EBP), which integrates empirical evidence, clinical expertise, as well as patient values toward achieving better nursing care of patients, professional responsibility, and system effectiveness. In spite of the prevailing scholarly propaganda and institutional support, EBP practice tends to be inconsistent and poorly synthesized in the clinical settings. This systematic literature review summarizes evidence presented in forty-five peer-reviewed articles published since 2010 through 2024, indicating that the obstacles to the integration of EBP are multi-factorial and comprise both individual- (i.e., knowledge and attitutinal gaps) and organizational (i.e., time constraints and resource unavailability) barriers as well as system-wide failures (i.e., incoherencies in education and policy inactivity). On the other hand, strong leadership, continuous training, institutional motivators, and regulatory alignment are other significant elements of the literature as the main drivers of effective implementation. Its conclusions highlight the necessity of comprehensive and context-relevant measures to help reduce the evidence-practice division in nursing. It suggests how teachers, healthcare managers, and policymakers can institutionalize EBP as one of the cultural and working norms at every level of the nursing profession. Keywords: Evidence-based practice; implementation of nursing; knowledge transfer; organizational culture; reform of education; health policy; translation of knowledge; research; utilization of research. Received Date: February 25, 2024 Accepted Date: March 12, 2024 Published Date: April 17, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/398 https://doi.org/10.5281/zenodo.15798359